Application of video-assisted thoracoscopic surgery (VATS) in the diagnosis of atipical hilar and mediastinal sarcoid lymphadenopathy: VATS in sarcoidosis - Meta Jevtović, Ivana; Miroslav (Medicinski časopis, 2021)
Sarcoidosis is a multisystem, granulomatous disease of unknown etiology. The inter-reaction of genetic and environmental factors is important in the disease development. The clinical presentation varies from asymptomatic to a form with nonspecific symptoms of the respiratory tract. The diagnosis is established according to the clinical manifestation, X-ray chest radiography as well as the computed tomography findings of hilar and or mediastinal lymphadenopathy with or without the presence of focal lesions in the lung parenchyma. The diagnosis is confirmed by histopathological finding of a non-caseating granuloma. Bronchoscopy with biopsy of lymph nodes and pleura is standard diagnostic method. Recently, video-assisted thoracoscopic surgery (VATS) is applied for more precise histopathological verification. The VATS method is indicated especially in case of the rapid disease progression where it is not possible to confirm the diagnosis by standard diagnostic procedures. We presented the case of 67 - year – old patient with radiographic findings of hilar and mediastinal lymphadenopathy as well as the progressive focal lesions of the lung parenchyma. The radiographic findings were detected on X-ray chest radiograph that was performed due to routine preoperative preparation of the patient for cholecystectomy. The patient was unsuccessfully treated with bronchoscopy. However, histopathological examination did not reveal the sarcoid origin of lymphadenopathy. Due to radiographic progression of lymphadenopathy, forming of bilateral pleural effusion with the focal lesions on the lung parenchyma, VATS was performed. Histopathological examination of biopsied lymph nodes of the mediastinum and pleura the diagnosis of sarcoid hilar and mediastinal lymphadenopathy was confirmed. The patient was treated with corticosteroids and four months after, the significant radiological as well as clinical regression were noticed. The VATS method is effective method in diagnosing of sarcoidosis-affected hilar and mediastinal lymphadenopathy, taking into account the patient’s safety.